2002
DOI: 10.1186/1297-9686-34-4-447
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of a major gene influencing ovulation in progeny of Lacaune meat sheep

Abstract: -Inheritance of the ovulation rate (OR) in the Lacaune meat breed was studied through records from a small nucleus of 36 hyper-prolific ewes screened on farms on the basis of their natural litter size, and from progeny data of three selected Lacaune sires. These sires were chosen at the AI centre according to their breeding values estimated for the mean and the variability of their daughters' litter size. Non-carrier Lacaune dairy ewes were inseminated to produce 121 F1 daughters and 27 F1 sons. Twelve sons (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 17 publications
1
15
0
2
Order By: Relevance
“…Progeny testing and a subsequent segregation analysis supported the earlier data and indicated the presence of an autosomal gene with one copy increasing the ovulation rate by 1.03 [24]. Further analysis of records from the subset of ewes and progeny test data from three rams and 12 of their sons in a backcross experiment enabled putative heterozygous and homozygous ewes to be compared and this indicated that the effect of the gene is additive for ovulation rate in a manner similar to that of the Booroola gene [4]. A genome scan localised the Lacaune gene to chromosome 11 and identified 10 markers around the Lacaune locus [24].…”
Section: Lacaunementioning
confidence: 50%
See 2 more Smart Citations
“…Progeny testing and a subsequent segregation analysis supported the earlier data and indicated the presence of an autosomal gene with one copy increasing the ovulation rate by 1.03 [24]. Further analysis of records from the subset of ewes and progeny test data from three rams and 12 of their sons in a backcross experiment enabled putative heterozygous and homozygous ewes to be compared and this indicated that the effect of the gene is additive for ovulation rate in a manner similar to that of the Booroola gene [4]. A genome scan localised the Lacaune gene to chromosome 11 and identified 10 markers around the Lacaune locus [24].…”
Section: Lacaunementioning
confidence: 50%
“…The presence of some ewes with extremely high ovulation rates led Bodin et al [4] to speculate that several alleles may be present or possibly other major genes within the screened group of ewes. Recently a mutation of BMP15, different from FecX I , FecX H , FecX G and FecX B , has been discovered in the Lacaune breed and work is in progress to determine the phenotype of ewes carrying this mutation (Bodin, personal communication).…”
Section: Lacaunementioning
confidence: 99%
See 1 more Smart Citation
“…1992), Woodlands ( FecX2 , Davis et al. 2001), Lacaune ( FecL , Bodin et al. 2002) and Wishart ( FecW , Davis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several strains exist, each being bred for a specific purpose – either milk for the dairy strain or suckling lamb for the meat strain. In the Lacaune meat breed population, inheritance of OR was hypothesized to be under the control of an autosomal gene of major additive effect named FecL (Bodin et al. 2002).…”
Section: Introductionmentioning
confidence: 99%